Effect of Fibre Supplementation on Body Weight and Composition, Frequency of Eating and Dietary Choice in Overweight Individuals - Solah, Vicky; Kerr, Deborah; Hunt, Wendy; Johnson, Stuart; Boushey, C.; Delp, E.; Meng, X.; Gahler, R.; James, Tony; Mukhtar, Syed Aqif; Fenton, Haylee; Wood, Simon (MDPI Publishing, 2017)
Fibre supplementation can potentially reduce energy intake and contribute to weight loss. The mechanism may be reduced frequency of eating, resulting in reduced food consumption. The objective of this research was to determine the effectiveness of fibre supplementation with PolyGlycopleX® (PGX®), on body weight and composition, frequency of eating and dietary intake in 118 overweight adults. In a three-arm, parallel, blind, randomised controlled trial participants were randomised to one of three groups; 4.5 g PGX as softgels (PGXS), 5 g PGX granules (PGXG) or 5 g rice flour (RF) control. Prior to supplementation and at 12 weeks, participants captured before and after images of all food and beverages consumed within 4 days using a mobile food record app (mFR). The mFR images were analysed for food group serving sizes and number of eating occasions. In the PGXG group, intention-to-treat analysis showed there was a significant reduction in waist circumference (2.5 cm; p = 0.003). Subgroup analysis showed that PGXG supplementation at the recommended dose resulted in a reduction in body weight (-1.4 ± 0.10 kg, p < 0.01), body mass index (BMI) reduction (-0.5 ± 0.10, p < 0.01), reduced number of eating occasions (-1.4 ± 1.2, p < 0.01) and a reduced intake of grain food (-1.52 ± 1.84 serves, p = 0.019). PGXG at the recommended dose resulted in a reduction in weight and BMI which was significantly greater than that for RF (p = 0.001). These results demonstrate the potential benefits of PGX fibre in controlling frequency of eating and in weight loss.